N and S concentration and stoichiometry in soybean during vegetative growth: Dynamics of indices for diagnosing the S status - Divito, Guillermo Adrián; Echeverria, Hernan Eduardo; Andrade, Fernando Hector; Sadras, Victor Oscar (Elsevier, 2019)
Information regarding the pattern of sulphur (S) accumulation in shoots is scarce for field crops and few comprehensive analysis were performed on N:S stoichiometry. Particularly, the need to study the patterns of uptake, allocation and stoichiometry of S and N in soybean is two-fold. First, the main areas for soybean production in the world have been recently reported as S-deficient. Second, S concentration (%S) and N:S ratios are relevant for diagnosing S deficiency. The aim of this work was to analyze, in a gradient of S availability, the dynamics of nitrogen concentration (%N), %S and N:S ratio in soybean lamina, stem and shoots during vegetative growth. Experiments were performed at Balcarce, Argentina during two growing seasons. Two soybean cultivars were evaluated: DM2200 (maturity group II) and DM4970 (maturity group IV), sown in optimum dates for the region (mid-November). DM2200 was also sown late (early January). We sampled crops between biomass ≈ 1 Mg ha−1 and R5. Shoots were separated in lamina, stem and petiole, and pod. The adjusted S dilution curve for S-sufficient treatments was attenuated in soybean (S = 2.8 W−0.11), with no differences among cultivars of maturity groups II and IV, and sowing dates from November to January. For the same treatments, the N:S ratio was stable in shoots during vegetative growth (N:S = 12.2), supporting the use of a unique threshold for diagnosing the S status during this period. Sulphur concentration in stems was more responsive to the availability of S than%S in lamina. In addition, the concentration of N in stem tended to be constant with variation in %S while %N and %S correlated in lamina. This produced a greater response of N:S in stem than in lamina. Thus, the determination of%S and N:S in stem are good candidates as indicators of S status of soybean.